Improved method of fundus photography for screening of diabetic retinopathy and maculopathy (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Fundus photography is the recommended procedure for screening of diabetic retinopathy according to recommendations of International Council of Ophthalmology (ICO). The purpose of our work was to investigate the possibilities of improved method of fundus photography for screening of diabetic retinpathy and maculopathy. Material and methods. Fundus photography was performed in patients with diabetes melitus in 7 standard zones according to ETDRS with the help of smartphone and lens for indirect ophthalmoscopy 20D. For fixation of the lens and smartphone the mobilephone holders were used, which were screwed to the horisontal bar with vertical handle, used for camera fixation in photography. With the help of application video recording was made with subsequent high quality still images extraction. Results. Presented technique of fundus photography allowed to aquire images of high quality. Conculsion. Described technique allows to obtain high quality images of retina for screening of diabetic retinopathy and maculopathy due to implementation of single instruments readily accessible in ophthalmological practice.
Keywords: diabetic maculopathy; diabetic retinopathy; screening; fundus photography